Probiotic bacteria inhibit the bovine respiratory pathogen Mannheimia haemolytica serotype 1 in vitro. (May 2017) - Amat, S.; Subramanian, S.; Timsit, E.; Alexander, T.W.
Abstract : Abstract: This study evaluated the potential of probiotic bacteria to inhibit growth and cell adhesion of the bovine respiratory pathogen Mannheimia haemoltyica serotype 1. The inhibitory effects of nine probiotic strains ( Lactobacillus acidophilus, Lactobacillus casei, Lactobacillus helveticus, Lactobacillus plantarum, Lactobacillus rhamnosus, Lactococcus lactis, Streptococcus thermophilus and two Paenibacillus polymyxa strains ) against M. haemolytica were evaluated using a spot‐on‐lawn method. Probiotic strains were then tested for their adherence to bovine bronchial epithelial (BBE) cells and the ability to displace and compete against M. haemolytica on BBE. Except for S. thermophilus, all probiotic strains inhibited the growth of M. haemolytica, with zones of inhibition ranging between 12 and 19 mm. Lactobacillus strains and Lactococcus lactis displayed greater ( P  <   0·05) BBE adhesion compared with M. heamolytica (8·3%) and other probiotics (<2·2%). Strains of P. polymyxa and L. acidophilus caused the greatest reduction in M. haemolytica adherence, through both displacement and competition, compared with other probiotics. The results of this study suggest that probiotics may have the potential to colonize the bovine respiratory tract, and exert antagonistic effects against M. haemolytica serotype 1. Significance and Impact of the Study: A common method to control bovine respiratory disease (BRD) in feedlots is through mass medication with antibiotics upon cattle entry (i.e. metaphylaxis). Increasingly, antimicrobial resistance in BRD bacterial pathogens has been observed in feedlots, which may have important implications for cattle health. In this study, probiotic strains were shown to adhere to bovine respiratory cells and inhibit the BRD pathogen M. haemolytica serotype 1 through competition and displacement. Probiotics may therefore offer a mitigation strategy to reduce BRD bacterial pathogens, in place of metaphylactic antimicrobials. Abstract : Significance and Impact of the Study: A common method to control bovine respiratory disease (BRD) in feedlots is through mass medication with antibiotics upon cattle entry (i.e. metaphylaxis). Increasingly, antimicrobial resistance in BRD bacterial pathogens has been observed in feedlots, which may have important implications for cattle health. In this study, probiotic strains were shown to adhere to bovine respiratory cells and inhibit the BRD pathogen M. haemolytica serotype 1 through competition and displacement. Probiotics may therefore offer a mitigation strategy to reduce BRD bacterial pathogens, in place of metaphylactic antimicrobials.